4x-7+2x=-7(1+3x)

Simple and best practice solution for 4x-7+2x=-7(1+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-7+2x=-7(1+3x) equation:



4x-7+2x=-7(1+3x)
We move all terms to the left:
4x-7+2x-(-7(1+3x))=0
We add all the numbers together, and all the variables
4x+2x-(-7(3x+1))-7=0
We add all the numbers together, and all the variables
6x-(-7(3x+1))-7=0
We calculate terms in parentheses: -(-7(3x+1)), so:
-7(3x+1)
We multiply parentheses
-21x-7
Back to the equation:
-(-21x-7)
We get rid of parentheses
6x+21x+7-7=0
We add all the numbers together, and all the variables
27x=0
x=0/27
x=0

See similar equations:

| 5x=11° | | 5x2x=-1 | | x*2+x-210=0 | | 5(y-8)+5=5y-35 | | 6=x/5+12 | | -7x-84=26-12x | | 2x^2+11x-434=0 | | z/6-2=1 | | x^2+x=3/4 | | 32.50t+5=28.75+20 | | 3x+15°=2x+4° | | 10(x+2)=140 | | 3.7x-4.6=1.2x+5.4 | | 0*x=9 | | x+7=18- | | 4. 10=2+x | | 2x^2+11x-444=0 | | 1/4x^2-5x-4=0 | | -1=-2x+2x | | 6x+8x=88 | | 2x-8+3x=5x+2 | | 7x-10=14+5x | | 9x+(80-x)=180 | | -5(2y-7)=75 | | 5(2x-1)-7(4x)=13 | | x/5+6=5 | | 146=2x^2 | | 3y+5.1=4.8 | | 9x+(80-x)=360 | | 12(5)−5y=−20 | | x+x+x+5=26 | | -10x+2=3+8x |

Equations solver categories